Second International Conference on a classification of ectodermal dysplasias: development of a multiaxis model - Salinas, Carlos F.; Irvine, Alan D.; Itin, Peter H.; Di Giovanna, John J.; Schneider, Holm; Clarke, Angus J.; Mcgovern, Laura Sternesky; Fete, Mary (American Journal of Medical Genetics Part A, 2014)
Ectodermal dysplasias (EDs) comprise a large clinically and etiologically heterogeneous group of genetic disorders characterized by abnormalities in tissues derived from the embryonic ectoderm. Controversy exists over which syndromes should be classified as EDs and which should be excluded from the classification. The challenge will be to balance comprehensiveness within the classification with usability and accessibility so that the benefits truly serve the needs of researchers, health-care providers, and ultimately the individuals and families directly affected by EDs. The overarching goal of the Second International Conference was to develop a consensus on EDs classifications, with the ultimate goal of creating a system that integrates clinical and molecular knowledge, using an interactive Internet-based database that clinicians, researchers, and laymen can use. The Conference, brought together a group of experts from around the world, including a diverse health-care providers, researchers, patient advocate representatives, and administrators. The Conference was modeled after the 2008 conference, with plenary sessions, scientific updates, and small group discussions. Based on the present clinical knowledge, new molecular advances and both coupled with new bioinformatics developments, the participants agree to develop a multi-axis system approach for the classification of EDs. The multi-axis approach will include a clinical/phenotype axis, a gene-based axis, and a functional/pathways axis. The significance of the conference outcomes includes, a new classification approach that will foster a better understanding of EDs, open new fields of research and develop a nosologic approach that may have broad implications for classifying other hereditary conditions.
EVALuna2:18896